Old wounds—new challenges: Women’s war experiences in the ex-Yugoslav and Bosnian armed conflict (1991–1995) - Bitunjac, Martina (Przegląd Krytyczny, 2022)
Women suffered greatly during the wars in the former Yugoslavia, particularly in Bosnia and Herzegovina. They lost everything they owned, they were widowed, had to flee, were victims of sexual violence or even lost their lives. Most have never gotten over their trauma from the war. Many of their tormentors have still never been brought to justice. At the same time, there were also women who supported the military conflict and ethnic hate as spreaders of propaganda, nationalists and war criminals. This article will explore the different fates and range of agencies open to women, who were to be sure primarily victims in the Balkan wars of the 1990s, but not just. It will also be shown how even after suffering brutal wartime experiences, women are now fighting for their rights and breaking open the patriarchal social structure existing up to today.